Innovative Approaches in Teaching Pencil Drawing in Higher Pedagogical Education - Sa’diyev Soli Tolipovich (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article explores innovative approaches in teaching pencil drawing within higher pedagogical education. The study emphasizes how incorporating modern teaching methods, including problem-based learning, collaborative projects, and digital technologies, enhances students’ artistic skills, creative thinking, and professional competencies. The research highlights the benefits of interactive and student-centered learning for developing aesthetic perception and independent problem-solving abilities.